Partisipasi Masyarakat Dalam Pengembangan Kampung Wisata Kampung Bandar Kota Pekanbaru - Lidya Bintang Christanti; Mayarni Mayarni (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
This research was conducted with the aim of finding out and explaining how community participation in the development of the Kampung Bandar tourist village and the inhibiting factors in implementing the development of the Kampung Bandar tourist village in Pekanbaru City. The theory used is the form of community participation according to Sutrata in the book Community Participation in Development which is divided into four types of participation, namely (1) Participation in Decision Making (2) Participation in Implementing Plans (3) Participation in enjoying the results (4) Participation in evaluation. The type of research used is descriptive qualitative, data collection techniques are obtained through observation, interviews and documentation. The results of this research show that in the decision-making stage, the community is involved, but holding meetings is only limited to activities in the tourist village, in implementing planned activities in the tourist village, the surrounding community will participate and have received attention and brought in tourists, as well as benefits from the development of the tourist village. Kampung Bandar has been felt by the local community because it can help the community's economy, but no evaluation has been carried out at this stage. The inhibiting factors are the lack of coordination and cooperation between existing human resources (HR), such as between the Pokdarwis and sub-districts, as well as among the Pokdarwis membership itself and there are still people who do not understand about the seven sapta of charms in the Kampung Bandar tourist village area.